Evaluation of Pleural Effusion Type Determination Based on Light's and Heffner's Criteria - Nordjannah Nordjannah; Ani Kartini; Darmawaty ER (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Pleural effusion is an abnormal accumulation of pleural fluid in the pleural cavity due to excessive transudation or exudation. Light's criteria is used as the standard method to distinguish between exudates and transudates. Some recent studies reported misclassifications which led to development of several alternative criteria, such as Heffner's criteria. The purpose of this study was to determine the sensitivity and specificity of Heffner's criteria to determine the type of pleural effusion. This research was an observational study with a cross-sectional method using a pleural effusion of patients at the Clinical Pathology Laboratory Installation at the Wahidin Sudirohusodo Hospital in July 2018. Total protein, LDH, and cholesterol levels were measured in all samples that met the inclusion and exclusion criteria. There were 45 pleural effusion samples that consisted of 30 transudate and 15 exudate samples. Based on clinical diagnosis, the Light's criteria showed 3 misclassifications and Heffner's criteria obtained showed 2 misclassifications. Based on the data above, the statistical data showed that Light's criteria had a sensitivity of 96.7% and specificity of 86.7%. Heffner's criteria had a sensitivity of 100% and specificity of 86.7%. Heffner's criteria can be used an alternative method to determine the type of pleural effusion because it showed a better sensitivity and specificity than Light's criteria.